Do Not Hallow until You Are out of the Wood! Ultrasonographic Detection of CPP Crystal Deposits in Menisci: Facts and Pitfalls - Georgios Filippou; Antonella Adinolfi; Panagiotis Bozios; Sauro Lorenzini; Valentina Picerno; Valentina Di Sabatino; Ilaria Bertoldi; Dario Gambera; Mauro Galeazzi; Bruno Frediani (The Scientific World Journal)
Purpose. Ultrasonography (US) has been demonstrated to be an important tool in the diagnosis of calcium pyrophosphate (CPP) crystal deposition disease. The aim of our study was to individuate and describe possible pitfalls in US detection of such deposits in menisci. Patients and Methods. We enrolled all patients waiting to undergo knee replacement surgery due to osteoarthritis, for one-month period. Each patient underwent US examination of the knee, focusing on the menisci. After surgery, the menisci were examined by US, macroscopically and microscopically, using the microscopic analysis as the gold standard for CPP deposition. Results. 11 menisci of 6 patients have been studied. Ex vivo examination of menisci performed better in CPP identification than in vivo examination. The possible reasons of misinterpretation or misdiagnosis of the in vivo exam were identified and are extensively described in the paper. Also a new sign of CPP crystal deposits was found. Conclusions. This study permitted to highlight some difficulties in CPP crystal detection by US in menisci. Further studies are needed to define completely US CPP crystal aspect and to improve the sensibility and specificity of US in CPP deposition diagnosis.